Effects of stiffness and configuration of brace-viscous damper systems on the response mitigation of offshore jacket platforms. (February 2021) - Vaezi, Mostafa; Pourzangbar, Ali; Fadavi, Manouchehr; Mousavi, Seyyed Mahmoud; Sabbahfar, Peyman; Brocchini, Maurizio
Abstract: We investigate the effects of a brace-viscous damper system on the dynamic response of offshore platforms. To do this, offshore jacket platforms with various distributions and three different configurations of brace-viscous damper systems - toggle, chevron, and diagonal configurations - and a wide range of brace stiffness are numerically modelled under the loading of irregular waves in ANSYS software. The dynamic response of the developed numerical model and its various brace-viscous damper configurations are validated against literature experimental and numerical results. Such a validation revealed an excellent agreement between the numerical results and the benchmark data. The results suggest that the standard deviation of the platform displacement given by a toggle configuration is less than that due to the chevron and diagonal configurations. Moreover, the maximum reduction of the base shear force is achieved by the application of the toggle configuration. Regarding the brace stiffness (area), for a reference damping coefficient of 500 N.m/s, a 54% increase in the brace area (from 42 to 91.8 mm 2 ) results in a 21.26%, 38.61%, and 17.57% reduction in the structure displacement response for the diagonal, chevron, and toggle configurations, respectively. Using the results of the numerical simulations, we propose the spatially-optimized distribution of the brace-viscous damper system. Comparing the numerical results of this paper with those of field observations it was shown that the viscous damper with toggle configuration outperforms both the viscoelastic damper and uncontrolled platforms in terms of dynamic response.